Effectiveness of Ear Acupressure on Anxiety Among Primigravida Women During Labor - Nurdiana, Ninik; Setiawandari; Waroh, Yuni Khoirul (Jurnal Ilmiah Kesehatan, 2026)
Childbirth is a physiological process that is influenced by maternal, familial, and environmental support. Primigravida women often experience heightened anxiety due to lack of childbirth experience. Increased anxiety can stimulate cortisol release, potentially leading to labor complications such as impaired uterine contractions and prolonged labor. One non-pharmacological approach to reduce anxiety during labor is acupressure. While ear acupressure has been shown to reduce labor pain, evidence regarding its effect on anxiety remains limited. This study aimed to examine the effectiveness of ear acupressure at the Shen Men point in reducing anxiety during the early stage of labor. A quasi-experimental one-group pre-test–post-test design was used, involving 31 primigravida women in early labor selected through convenience sampling. Anxiety levels were measured before and after the intervention using the Anxiety Assessment Scale for Women in Labor (AASWL). Before the intervention, 67.70% of participants reported anxiety levels above 50%. After ear acupressure, more than half of the participants (54.80%) continued to report anxiety levels above 50%. The mean anxiety score decreased from 25.71 before the intervention to 16.48 after, showing an average reduction of 9.23 points. However, statistical analysis using the Wilcoxon signed-rank test yielded a p-value of 0.157, indicating that the reduction was not statistically significant. In conclusion, ear acupressure at the Shen Men point was not shown to have a significant effect on reducing anxiety during the first stage of labor in primigravida women.